Mast Cell Migration and Chemotaxis Assayed by Microscopy - Bambousková, Monika; Rubíková, Zuzana; Dráberová, Lubica; Dráber, Pavel; Dráber, Petr (Methods in molecular biology (Clifton, N.J.), 2020)
A better understanding of the molecular mechanisms leading to mast cell migration and chemotaxis is the long-term goal in mast cell research and is essential for comprehension of mast cell function in health and disease. Various techniques have been developed in recent decades for in vitro and in vivo assessment of mast cell motility and chemotaxis. In this chapter, three microscopy assays facilitating real-time quantification of mast cell chemotaxis and migration are described, focusing on individual cell tracking and data analysis.
Keywords: buněčný tracking; sefarosa; fibronektiny; Cell Migration Assays; počítačové systémy; Mast Cells; Chemoattractant; Mast cells; Computer Systems; Biological Assay; Microscopy; Chemokine; Software; biotest; Cell Movement; analýza buněčné migrace; Animals; lidé; Cell migration; mikroskopie; Sepharose; Humans; zvířata; mastocyty; pohyb buněk; myši; Cell tracking; software; Mice; Chemotaxis; prostředí kontrolované; Fibronectins; Cell Tracking; chemotaxe; Environment, Controlled